Wspólna polityka zagraniczna i bezpieczeństwa na tle działań zewnętrznych Unii Europejskiej - Cybulski, Leszek (Common Foreign and Security Policy Against the Background of the EU External Actions, 2008)
This paper presents a description and systematization of the scope of the European Union external activities as well as legal, institutional and financial arrangements which enable the EU to act externally. It also describes the principal dilemmas with regard to contemporary tasks and the future of the Common Foreign and Security Policy (CFSP). To this respect, the segmentation of countries has been made and it is demonstrated that there are different depth levels of political and economic links between the European Union and countries (territories) of the world. The evidence of the above is the versatile level of financial support within the framework of particular co-operation forms as well as scopes of bilateral and multilateral agreements. It serves a purpose of security, stability and prosperity in closer and further environment of the EU.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 236-259